Method for preparing coal-based porous carbon through deep eutectic solvent swelling-functionalization
The use of low eutectic solvents for swelling-functionalization of coal simplifies the preparation of porous carbon, addressing high costs and environmental issues while producing high-performance materials for energy storage.
Patent Information
- Application Number
- CN202411296615.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
AI Technical Summary
The preparation of high-performance porous carbon materials from coal is hindered by the complexity of coal structure and high ash content, leading to high costs and environmental pollution in existing pretreatment methods.
A method involving the use of low eutectic solvents for swelling-functionalization of coal, comprising mixing a hydrogen bond donor and acceptor, treating coal with a low eutectic solvent, and heat-treating under inert conditions to produce coal-based porous carbon.
The method simplifies the preparation process, reduces costs, minimizes environmental impact, and produces porous carbon with a developed pore structure and high specific surface area suitable for energy storage devices.
Smart Images

Figure CN119240657A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of coal-based porous carbon materials for supercapacitors, and in particular relates to a method for preparing coal-based porous carbon by swelling-functionalization with a low eutectic solvent. Background Art
[0002] my country has abundant reserves of coal resources, which are important carbon material precursors with high value utilization. When porous carbon electrodes are prepared directly from coal as a carbon precursor, it is difficult to obtain high-performance porous carbon materials due to the complexity of the coal structure and the high ash content. Therefore, pretreatment of coal is one of the effective methods for preparing high-performance electrode materials. Common pretreatment methods include pre-oxidation, solvent extraction, and acid deashing. However, the above pretreatment methods also have problems such as high cost, complex post-treatment, and environmental pollution. Therefore, exploring green and efficient pretreatment methods has important research value and practical significance.
[0003] As a kind of ionic liquid, deep eutectic solvents (DESs) have similar properties to ionic liquids, and their preparation process is simpler than that of ionic liquids. Due to the diversity of DESs components, they can not only be used as solvents to pretreat coal, but also as functional agents to prepare coal-based porous carbon materials. Applying them to new energy system supercapacitors can greatly reduce the cost of devices and lay the foundation for their commercial production. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing coal-based porous carbon by swelling-functionalization with a low eutectic solvent, simplify the preparation process of coal-based porous carbon, and solve the problems of high cost and environmental pollution in the existing preparation of coal-based porous carbon materials.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions:
[0006] A method for preparing coal-based porous carbon by swelling-functionalization with a low eutectic solvent comprises the following steps:
[0007] 1) mixing a hydrogen bond donor and a hydrogen bond acceptor in a molar ratio of 1:(1-10), placing in an oil bath at 50-150° C. and stirring until a clear and transparent liquid is formed;
[0008] 2) taking coal with a mesh size of less than 200, putting it into a glass bottle and sealing it, then adding the liquid obtained in step 1), the volume ratio of coal to the liquid obtained in step 1) being 1:(1-20), stirring evenly with magnetic force at a speed of 100-500 r / min, and placing the glass bottle in an oil bath at 25-120° C. for 1-24 hours;
[0009] 3) taking the mixture obtained in step 2) out of the glass bottle and placing it in a corundum crucible with a cover, placing the corundum crucible containing the mixture in the middle heating area of a tubular furnace, and performing heat treatment under an inert atmosphere, heating the temperature of the tubular furnace to 600-900° C. at a heating rate of 1-10° C. / min and maintaining the temperature for 1-3 hours, cooling to room temperature, and then washing and drying.
[0010] The hydrogen bond donor is polyol or amide.
[0011] The hydrogen bond acceptor is one of metal halides, carbonates and quaternary ammonium salts.
[0012] The coal is Xinjiang lignite or bituminous coal.
[0013] The inert atmosphere is nitrogen or argon.
[0014] The coal is ground by a ball mill and dried at 60-105° C. under normal pressure for 10-20 hours to obtain the coal.
[0015] The coal in step 2) is 0.5 g, and the liquid obtained in step 1) is 0.5-5 mL.
[0016] The washing in step 3) is washing with 1M hydrochloric acid solution at least twice, and then washing with distilled water until neutral.
[0017] The drying in step 3) is carried out by placing the product in a forced air drying oven at 80 to 100° C. for 20 to 30 hours.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. Abundant raw materials: The coal used in the present invention is cheap and easy to obtain, and the processing process is simple. The raw materials for preparing the low eutectic solvent are widely available and inexpensive, which makes the manufacturing cost of the low eutectic solvent relatively low.
[0020] 2. Flexibility: The diversity of the components of the low eutectic solvent can flexibly adjust the effect of the low eutectic solvent on coal swelling by controlling the types and proportions of the components.
[0021] 3. Environmental protection and high efficiency: The present invention adopts a low eutectic solvent as a swelling agent and a functionalizing agent, which avoids the corrosion of equipment and subsequent complicated treatment processes caused by the use of a large amount of deashing solvents, activators, etc. in the traditional method, and has the advantages of environmental protection and high efficiency.
[0022] 4. Excellent performance: The prepared coal-based porous carbon material has a developed pore structure, high specific surface area and good conductivity, and is suitable for electrode materials of energy storage devices such as supercapacitors.
[0023] 5. Simple process: The preparation method of the present invention is simple, easy to realize industrial production, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the original coal in Example 1.
[0025] Figure 2 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon of Example 1.
[0026] Figure 3 This is a scanning electron micrograph (SEM) of the coal obtained by swelling with manganese chloride-ethylene glycol DES in Example 1.
[0027] Figure 4 This is a scanning electron microscopy (SEM) image of the coal-based porous carbon obtained by swelling with manganese chloride-ethylene glycol DES in Example 1.
[0028] Figure 5 (a) and (b) are cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by swelling and functionalization of manganese chloride-ethylene glycol DES in Example 1 tested in a three-electrode system.
[0029] Figure 6 This is a scanning electron micrograph (SEM) of the coal obtained by swelling with ferric chloride-ethylene glycol DES in Example 2.
[0030] Figure 7 This is a scanning electron microscopy (SEM) image of the coal-based porous carbon obtained by swelling with ferric chloride-ethylene glycol DES in Example 2.
[0031] Figure 8 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by ferric chloride-ethylene glycol DES swelling-functionalization in Example 2 tested in a three-electrode system.
[0032] Fig. 9 This is a scanning electron micrograph (SEM) of the coal obtained by swelling with cobalt chloride-ethylene glycol DES in Example 3.
[0033] Fig.10 This is a scanning electron microscopy (SEM) image of the coal-based porous carbon obtained by swelling with cobalt chloride-ethylene glycol DES in Example 3.
[0034] Fig.11 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by swelling-functionalization with cobalt chloride-ethylene glycol DES in Example 3 tested in a three-electrode system.
[0035] Fig.12This is a scanning electron micrograph (SEM) of the coal obtained by swelling with nickel chloride-ethylene glycol DES in Example 4.
[0036] Fig.13 This is a scanning electron microscopy (SEM) image of the coal-based porous carbon obtained by swelling with nickel chloride-ethylene glycol DES in Example 4.
[0037] Fig.14 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by swelling-functionalization with nickel chloride-ethylene glycol DES in Example 4 tested in a three-electrode system.
[0038] Fig.15 This is a scanning electron micrograph (SEM) of the coal obtained by swelling with copper chloride-ethylene glycol DES in Example 5.
[0039] Fig.16 This is a scanning electron microscopy (SEM) image of the coal-based porous carbon obtained by swelling with copper chloride-ethylene glycol DES in Example 5.
[0040] Fig.17 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by copper chloride-ethylene glycol DES swelling-functionalization in Example 5 tested in a three-electrode system.
[0041] Fig.18 This is a scanning electron micrograph (SEM) of the coal obtained by swelling with zinc chloride-ethylene glycol DES in Example 6.
[0042] Fig.19 This is a scanning electron microscopy (SEM) image of the coal-based porous carbon obtained by swelling with zinc chloride-ethylene glycol DES in Example 6.
[0043] Fig. 20 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by zinc chloride-ethylene glycol DES swelling-functionalization in Example 6 tested in a three-electrode system.
[0044] Fig.21 This is a scanning electron micrograph (SEM) of the coal obtained by swelling with choline chloride-urea DES in Example 7.
[0045] Fig. 22 This is a scanning electron microscopy (SEM) image of the coal-based porous carbon obtained by swelling with choline chloride-urea DES in Example 7.
[0046] Fig.23(a) and (b) are cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by swelling and functionalization with choline chloride-urea DES in Example 7 tested in a three-electrode system.
[0047] Fig.24 This is a scanning electron micrograph (SEM) of the coal obtained by swelling with potassium carbonate-ethylene glycol DES in Example 8.
[0048] Fig.25 This is the XRD spectrum of the raw coal in Example 8.
[0049] Fig.26 This is the XRD spectrum of coal obtained by swelling with potassium carbonate-ethylene glycol DES in Example 8.
[0050] Fig. 27 This is a scanning electron microscope (SEM) image of the coal-based porous carbon obtained by potassium carbonate-ethylene glycol DES swelling-functionalization in Example 8.
[0051] Fig.28 This is the X-ray photoelectron spectrum of the coal-based porous carbon obtained by potassium carbonate-ethylene glycol DES swelling-functionalization in Example 8.
[0052] Fig.29 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by swelling and functionalization of potassium carbonate-ethylene glycol DES in Example 8 tested in a three-electrode system.
[0053] Fig.30 (a) and (b) are the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the bituminous coal-based porous carbon obtained by swelling and functionalization of potassium carbonate-ethylene glycol DES in Example 9 tested in a three-electrode system.
[0054] Fig.31 (a) and (b) are the constant current charge-discharge (GCD) curve and the Lagung curve of the button cell in Example 10 in an alkaline electrolyte (6M KOH).
[0055] Fig.32 (a) and (b) are the button cell in Example 10 in a neutral electrolyte (1M Na 2 SO 4 ) in the constant current charge and discharge (GCD) curve and Lagung curve diagram. DETAILED DESCRIPTION
[0056] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0057] Example 1
[0058] Using 200 mesh Kuche coal (lignite) as raw material, the scanning electron microscope results of lignite are as follows: Figure 1 0.5g lignite was directly carbonized to 800℃ and kept for 2 hours. After washing and drying, the material was prepared into an electrode sheet. The electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Figure 2 As shown, this sample is a comparative example.
[0059] Method for preparing coal-based porous carbon by swelling-functionalization with a low eutectic solvent:
[0060] 200 mesh Kuche coal (lignite) was used as raw material, and manganese chloride-ethylene glycol type DES was used as swelling agent and functional agent. Manganese chloride and ethylene glycol were placed in a glass bottle at a molar ratio of 1:8 and heated in an oil bath at 80°C at 500 rpm s -1 Stir at a high speed until a clear solution is formed, which is manganese chloride-ethylene glycol type DES.
[0061] 0.5 g of coal was placed in a glass bottle, and 0.5-5 mL of manganese chloride-ethylene glycol DES was added. The coal and the low eutectic solvent were mixed evenly using a magnetic stirrer (speed 100-500 r / min), and the glass bottle was placed in an oil bath at 100°C for 4 hours. The scanning electron microscopy results of the coal after swelling were as follows: Figure 3 As shown. Subsequently, the mixture was placed in a quartz boat, placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, the sample was washed and dried to obtain the final product. The scanning electron microscopy results of the final product are shown in Figure 4 The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Figure 5 As shown. Figure 1 and Figure 3 It can be seen that after the coal is swollen by manganese chloride-ethylene glycol DES, the morphology becomes rough. The morphology of the coal-based porous carbon obtained by swelling with manganese chloride-ethylene glycol DES is as follows Figure 4 As shown, it presents a flake-like morphology. Figure 2 and 5 It can be seen that the specific capacity of coal-based porous carbon is 55F g -1 The specific capacity of coal-based porous carbon obtained by swelling with manganese chloride-ethylene glycol type DES is 134Fg -1 .
[0062] Example 2
[0063] 200 mesh Kuche coal (lignite) was used as raw material, and ferric chloride-ethylene glycol type DES was used as swelling agent and functional agent. Ferric chloride and ethylene glycol were placed in a glass bottle at a molar ratio of 1:8 and heated in an oil bath at 80°C at 500 rpm s -1 Stir at a high speed until a clear solution is formed, which is ferric chloride-ethylene glycol DES. Put 0.5g of coal into a glass bottle, add 0.5-5mL of ferric chloride-ethylene glycol DES, use a magnetic stirrer to mix the coal and the low eutectic solvent evenly, and then put the glass bottle into a 100℃ oil bath for 4 hours. The scanning electron microscopy results of the coal after swelling are as follows: Figure 6 As shown. Subsequently, the mixture was placed in a quartz boat, placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, the sample was washed and dried to obtain the final product. The scanning electron microscopy results of the final product are shown in Figure 7 The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Figure 8 As shown. Figure 1 and Figure 6 It can be seen that the morphology of coal becomes rough after swelling with ferric chloride-ethylene glycol DES. Figure 7 As shown, it presents a flake-like morphology. Figure 8 It can be seen that the specific capacity of the coal-based porous carbon obtained by swelling the ferric chloride-ethylene glycol type DES is 163F g -1 .
[0064] Example 3
[0065] 200 mesh Kuche coal (lignite) was used as raw material, and cobalt chloride-ethylene glycol type DES was used as swelling agent and functional agent. Cobalt chloride and ethylene glycol were placed in a glass bottle at a molar ratio of 1:8 and heated in an oil bath at 80°C at 500 rpm s -1 Stir at a high speed until a clear solution is formed, which is cobalt chloride-ethylene glycol type DES. Put 0.5g of coal into a glass bottle, add 0.5-5mL of cobalt chloride-ethylene glycol type DES, use a magnetic stirrer to mix the coal and the low eutectic solvent evenly, and then put the glass bottle into a 100℃ oil bath for 4 hours. The scanning electron microscopy results of the coal after swelling are as follows: Fig. 9 As shown. Subsequently, the mixture was placed in a quartz boat, placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, the sample was washed and dried to obtain the final product. The scanning electron microscopy results of the final product are shown in Fig.10 The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Fig.11 As shown. Figure 1 and Fig. 9 It can be seen that the morphology of coal becomes rough after swelling with cobalt chloride-ethylene glycol DES. Fig.10 As shown, it presents a flake-like morphology. Fig.11 It can be seen that the specific capacity of the coal-based porous carbon obtained by swelling the cobalt chloride-ethylene glycol type DES is 94F g -1 .
[0066] Example 4
[0067] 200 mesh Kuche coal (lignite) was used as raw material, and nickel chloride-ethylene glycol type DES was used as swelling agent and functional agent. Nickel chloride and ethylene glycol were placed in a glass bottle at a molar ratio of 1:8 and heated in an oil bath at 80°C at 500 rpm s -1 Stir at a high speed until a clear solution is formed, which is nickel chloride-ethylene glycol DES. Put 0.5g of coal into a glass bottle, add 0.5-5mL of nickel chloride-ethylene glycol DES, use a magnetic stirrer to mix the coal and the low eutectic solvent evenly, and then put the glass bottle into an oil bath at 100℃ for 4 hours. The scanning electron microscopy results of the coal after swelling are as follows: Fig.12 As shown. Subsequently, the mixture was placed in a quartz boat, placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, the sample was washed and dried to obtain the final product. The scanning electron microscopy results of the final product are shown in Fig.13 The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Fig.14 As shown. Figure 1 and Fig.12 It can be seen that the morphology of coal becomes rough after swelling with nickel chloride-ethylene glycol DES. Fig.13 As shown, it exhibits a flake-like morphology. Fig.14 It can be seen that the specific capacity of the coal-based porous carbon obtained by swelling nickel chloride-ethylene glycol type DES is 80F g -1 .
[0068] Example 5
[0069] 200 mesh Kuche coal (lignite) was used as raw material, and copper chloride-ethylene glycol type DES was used as swelling agent and functional agent. Copper chloride and ethylene glycol were placed in a glass bottle at a molar ratio of 1:8 and heated in an oil bath at 80°C at 500 rpm s -1Stir at a high speed until a clear solution is formed, which is copper chloride-ethylene glycol DES. Put 0.5g of coal into a glass bottle, add 0.5-5mL of copper chloride-ethylene glycol DES, use a magnetic stirrer to mix the coal and the low eutectic solvent evenly, and then put the glass bottle into a 100℃ oil bath for 4 hours. The scanning electron microscopy results of the coal after swelling are as follows: Fig.15 As shown. Subsequently, the mixture was placed in a quartz boat, placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, the sample was washed and dried to obtain the final product. The scanning electron microscopy results of the final product are shown in Fig.16 The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Fig.17 As shown. Figure 1 and Fig.15 It can be seen that after the coal is swollen by copper chloride-ethylene glycol DES, the morphology becomes rough. The morphology of the coal-based porous carbon obtained by swelling with copper chloride-ethylene glycol DES is as follows Fig.16 As shown, it exhibits a flake-like morphology. Fig.17 It can be seen that the specific capacity of the coal-based porous carbon obtained by swelling copper chloride-ethylene glycol type DES is 83F g -1 .
[0070] Example 6
[0071] 200 mesh Kuche coal (lignite) was used as raw material, zinc chloride-ethylene glycol type DES was used as swelling agent and functional agent. Zinc chloride and ethylene glycol were placed in a glass bottle at a molar ratio of 1:8 and heated in an oil bath at 80°C at 500 rpm s -1 Stir at a high speed until a clear solution is formed, which is zinc chloride-ethylene glycol type DES. Put 0.5g of coal into a glass bottle, add 0.5-5mL of zinc chloride-ethylene glycol type DES, use a magnetic stirrer to mix the coal and the low eutectic solvent evenly, and then put the glass bottle into a 100℃ oil bath for 4 hours. The scanning electron microscopy results of the coal after swelling are as follows: Fig.18 As shown. Subsequently, the mixture was placed in a quartz boat, placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, the sample was washed and dried to obtain the final product. The scanning electron microscopy results of the final product are shown in Fig.19 The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Fig. 20 As shown. Figure 1 and Fig.18 It can be seen that the morphology of coal becomes rough after swelling with zinc chloride-ethylene glycol DES. Fig.19 As shown, it presents a bulk morphology. Fig. 20 It can be seen that the specific capacity of the coal-based porous carbon obtained by swelling zinc chloride-ethylene glycol type DES is 99F g -1 .
[0072] Example 7
[0073] 200 mesh Kuche coal (lignite) was used as raw material, and choline chloride-urea type DES was used as swelling agent and functional agent. Choline chloride and urea were placed in a glass bottle at a molar ratio of 1:2 and heated in an oil bath at 80°C at 500 rpm s -1 Stir at a high speed until a clear solution is formed, which is choline chloride-urea DES. 0.5 g of coal is placed in a glass bottle and 0.5-5 mL of choline chloride-urea DES is added. The coal and the low eutectic solvent are mixed evenly using a magnetic stirrer. Subsequently, the glass bottle is placed in an 80°C oil bath for 6 hours. The scanning electron microscopy results of the swollen coal are as follows: Fig.21 As shown. Subsequently, the mixture was placed in a quartz boat, placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, the sample was taken out and washed and dried to obtain the final product. The scanning electron microscopy results of the final product are shown in Fig. 22 The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Fig.23 As shown. Figure 1 and Fig.21 It can be seen that the morphology of coal becomes rough after swelling with choline chloride-urea DES. Fig. 22 As shown, it presents a bulk morphology. Fig.23 It can be seen that the specific capacity of the coal-based porous carbon obtained by swelling the choline chloride-urea type DES is 94 F g -1 .
[0074] Example 8
[0075] 200 mesh Kuche coal (lignite) was used as raw material, and potassium carbonate-ethylene glycol type DES was used as swelling agent and functional agent. Potassium carbonate and ethylene glycol were placed in a glass bottle at a molar ratio of 1:8 and heated in an oil bath at 80°C at 500 rpm s -1 Stir at a high speed until a clear solution is formed, which is potassium carbonate-ethylene glycol type DES. Put 0.5g of coal into a glass bottle, add 0.5-5mL of potassium carbonate-ethylene glycol type DES, use a magnetic stirrer to mix the coal and the low eutectic solvent evenly, and then put the glass bottle into a 100℃ oil bath for 4 hours. The scanning electron microscopy results of the coal after swelling are as follows: Fig.24 The XRD spectra of the raw coal and the swollen coal are shown in Fig.25 and 26 As shown, it was detected that the characteristic peaks of minerals in the coal disappeared after swelling. The mixture was then placed in a quartz boat and placed in a tube furnace and heated to 700°C at a rate of 5°C / min for 2 hours. After cooling naturally to room temperature, the sample was taken out and washed and dried to obtain the final product. The scanning electron microscopy results of the obtained sample are shown in Fig. 27 As shown, the X-ray photoelectron spectrum of the test is as follows Fig.28 As shown in the figure, a high content of O element was detected in the sample. The final product was prepared into an electrode sheet, and the electrochemical performance of the material was tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves are shown in Fig.29 As shown. Figure 1 and Fig.24 It can be seen that the morphology of coal becomes rough after swelling with potassium carbonate-ethylene glycol type DES. Fig.25 and Fig.26 The XRD spectrum shows that after the coal is swollen by potassium carbonate-ethylene glycol DES, the mineral peak disappears, indicating that potassium carbonate-ethylene glycol DES swelling effectively removes impurities in the coal. The morphology of the coal-based porous carbon obtained by potassium carbonate-ethylene glycol DES swelling is shown in Figure 2. Fig. 27 As shown, it exhibits a porous carbon morphology. Fig.28 The XPS spectrum shows that the coal-based porous carbon obtained by swelling with potassium carbonate-ethylene glycol type DES contains two elements: C and O. Fig.29 It can be seen that the specific capacity of coal-based porous carbon obtained by swelling potassium carbonate-ethylene glycol type DES is 362Fg -1 .
[0076] Example 9
[0077] Take 200-mesh Heishan coal (bituminous coal) as raw material, and potassium carbonate-ethylene glycol type DES as swelling agent and functionalizing agent. The preparation method of potassium carbonate-ethylene glycol type DES is the same as the swelling agent and functionalizing agent in Example 8. Put 0.5g of coal into a glass bottle, add 0.5-5mL potassium carbonate-ethylene glycol type DES, use a magnetic stirrer to mix the coal and the low eutectic solvent evenly, and then put the glass bottle into an oil bath at 100°C for 4 hours. Then put the mixture into a quartz boat, put it into a tube furnace, and heat it to 800°C at a heating rate of 5°C / min for 2 hours. After naturally cooling to room temperature, take out the sample and wash and dry it to obtain the final product. The final product is prepared into an electrode sheet, and the electrochemical properties of the material are tested using a three-electrode system. The cyclic voltammetry (CV) and constant current charge and discharge (GCD) curves are shown in Fig.30 shown. Fig.29 It can be seen that the specific capacity of coal-based porous carbon obtained by swelling potassium carbonate-ethylene glycol type DES is 191F g -1 .
[0078] Example 10
[0079] The product obtained in Example 8 was used as the electrode material to make supercapacitor electrodes, and nickel foam was used as the current collector. A 12 mm diameter disc was cut using a slicer, and 2 mg of the electrode material was weighed and mixed with acetylene black and PTFE to form a slurry, which was evenly applied on a 12 mm diameter nickel foam. A tablet press was used to apply a pressure of 10 MPa to press the electrode sheet. The supercapacitor was assembled using a 2016 battery shell, and the electrode sheets coated with the electrode material were used as the positive and negative electrodes, respectively, with a glass fiber separator in between, and the electrolytes were 6 M KOH solution and 1 M Na 2 SO 4 The solution was used to seal the battery with a pressure of 10 MPa using a battery sealer. Finally, the battery performance was tested using an electrochemical workstation and a battery testing system. The results were as follows: Fig.31 and 32 shown. Fig.31 It can be seen that the energy density of the device assembled by the electrode material of Example 8 with 6M KOH as the electrolyte can reach 8.99Whkg -1 . Fig.32 It can be seen that the electrode material of Example 8 is 1M Na 2 SO 4 The energy density of the device assembled for the electrolyte can reach 21.9Wh kg -1 .
Claims
1. A method for preparing coal-based porous carbon by swelling-functionalization with a low eutectic solvent, characterized in that: The following steps are involved: 1) mixing a hydrogen bond donor and a hydrogen bond acceptor in a molar ratio of 1:(1-10), placing in an oil bath at 50-150° C. and stirring until a clear and transparent liquid is formed; 2) taking coal with a mesh size of less than 200, putting it into a glass bottle and sealing it, then adding the liquid obtained in step 1), the volume ratio of coal to the liquid obtained in step 1) being 1:(1-20), stirring evenly with magnetic force at a speed of 100-500 r / min, and placing the glass bottle in an oil bath at 25-120° C. for 1-24 hours; 3) taking the mixture obtained in step 2) out of the glass bottle and placing it in a corundum crucible with a cover, placing the corundum crucible containing the mixture in the middle heating area of a tubular furnace, and performing heat treatment under an inert atmosphere, heating the temperature of the tubular furnace to 600-900° C. at a heating rate of 1-10° C. / min and maintaining the temperature for 1-3 hours, cooling to room temperature, and then washing and drying.
2. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The hydrogen bond donor is polyol or amide.
3. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The hydrogen bond acceptor is one of metal halides, carbonates and quaternary ammonium salts.
4. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The coal is Xinjiang lignite or bituminous coal.
5. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The inert atmosphere is nitrogen or argon.
6. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The coal is ground by a ball mill and dried at 60-105° C. under normal pressure for 10-20 hours to obtain the coal.
7. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The coal in step 2) is 0.5 g, and the liquid obtained in step 1) is 0.5-5 mL.
8. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The washing in step 3) is washing with 1M hydrochloric acid solution at least twice, and then washing with distilled water until neutral.
9. The method for preparing coal-based porous carbon by swelling-functionalization with a deep eutectic solvent according to claim 1, characterized in that: The drying in step 3) is carried out by placing the product in a forced air drying oven at 80 to 100° C. for 20 to 30 hours.
